The Impact of Customer Reviews, Hotel Location, and Hotel Price Towards Potential Guests’ Intent to Stay at the Ritz- Carlton, Bali - Annarica Tisna; Finny Chianata; Joselyn Chandrigo; Michelle Christy; Valerie (International Journal of Economics, Business Management and Accounting (IJEBMA), 2019)
This study examines the influence of customer reviews, hotel location, and hotel price on the intent of potential guests to stay at The Ritz-Carlton, Bali. Through a mixed-methods approach involving surveys, online reviews, and interviews, the research reveals that positive customer reviews significantly contribute to the likelihood of intent to stay, emphasizing the role of online word-of-mouth. Additionally, favorable hotel location emerges as a key driver for guest intent, while the relationship between hotel price and intent proves more complex, indicating a willingness to pay premium prices for positive reviews and desirable locations. These findings provide insights for strategic decision-making in hospitality marketing and management